Use of statins and risk of fractures. - van Staa, T; Wegman, S; de Vries, F; Leufkens, B; Cooper, C (2001)
CONTEXT: Previous studies have reported lower fracture risks in patients taking 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors (statins). OBJECTIVE: To investigate risk of fracture among statin users. DESIGN: Case-control study of data from the General Practice Research Database (GPRD). SETTING: A total of 683 general clinical practices in the United Kingdom. PATIENTS: Cases were 81 880 patients aged 50 years or older who had a fracture of the vertebrae, clavicle, humerus, radius/ulna, carpus, hip, ankle, or foot occurring between the enrollment date of their practice into the GPRD and July 1999, paired with 81 880 age-, sex-, and practice-matched controls. MAIN OUTCOME MEASURE: Risk of fracture in current users vs nonusers of statins. Odds ratios were estimated from conditional logistic regression and adjusted for smoking, medications and illnesses associated with fracture risk, and body mass index when known. RESULTS: The adjusted odds ratio (OR) for current use of statins compared with nonuse was 1.01 (95% confidence interval [CI], 0.88-1.16). For forearm, hip, and vertebral fractures, the ORs were 1.01 (95% CI, 0.80-1.27), 0.59 (95% CI, 0.31-1.13), and 1.15 (95% CI, 0.62-2.14), respectively. Relative to nonuse, a statin dosage of less than 20 mg/d (standardized to simvastatin) was associated with an adjusted OR of fracture of 1.13 (95% CI, 0.96-1.33); this OR was 1.07 (95% CI, 0.82-1.38) at dosages of 20 to 39.9 mg/d and 0.85 (95% CI, 0.47-1.53) at dosages of 40 mg/d or more. The adjusted OR was 0.71 (95% CI, 0.50-1.01) for statin use durations of 0 to 3 months, 1.31 (95% CI, 0.87-1.95) for durations of 3 to 6 months, 1.14 (95% CI, 0.82-1.58) for durations of 6 to 12 months, and 1.17 (95% CI, 0.99-1.40) for durations of more than 12 months. CONCLUSION: In this study, use of statins at dosages prescribed in clinical practice was not associated with a reduction in risk of fracture.